Construction of 2D nanoporous networks by coupling on-surface dynamic imine chemistry and dipole-stabilized self-assembly. Issue 2 (13th December 2016) - Yue, Jie-Yu; Markoulides, Marios; Regan, Andrew C.; Li, Shu-Ying; Chronakis, Nikos; Gourdon, André; Chen, Ting; Yan, Hui-Juan; Wang, Dong
Abstract : Double-walled nanoporous networks based on the Schiff base reaction of nonplanar tripodic building blocks and subsequent dipole-directed self-assembly were fabricated on highly oriented pyrolytic graphite (HOPG). Abstract : Double-walled nanoporous networks based on the Schiff base reaction of nonplanar tripodic building blocks and subsequent dipole-directed self-assembly were fabricated on highly oriented pyrolytic graphite (HOPG) at the gas–solid interface. This is the first example of nonplanar molecules exploited as precursors for a surface reaction.